2008
DOI: 10.1111/j.1471-6402.2008.00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Excessive Body Weight, and Psychological Well-Being in Adulthood

Abstract: We examined gender differences in the association between body mass index (BMI) and psychological well-being. Regression analysis involving 3,251 adults indicated that gender moderated the BMI-psychological well-being link. In follow-up analyses, higher BMI predicted lower psychological well-being only among women. When participants were categorized into 5 BMI groups, women reported lower psychological well-being than men in the overweight and obese I groups, but no gender differences were observed in the more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
46
1
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 44 publications
2
46
1
4
Order By: Relevance
“…This revealed the existence of a higher-order PWB factor [11,13,20]. In the present research, only AU and EM exhibited trivial noninvariance in the factor mean; therefore, it is reasonable to infer that the mean difference of the higher-order PWB factor between genders is inclined toward invariance.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This revealed the existence of a higher-order PWB factor [11,13,20]. In the present research, only AU and EM exhibited trivial noninvariance in the factor mean; therefore, it is reasonable to infer that the mean difference of the higher-order PWB factor between genders is inclined toward invariance.…”
Section: Discussionmentioning
confidence: 68%
“…Other studies have also revealed this problem [8][9][10][11][12]. To avoid this problem, some studies have used a total score instead of each subscore of PWB to detect gender differences [11,13]. To enhance the reliability of each subscale, Li [14] selected another 18 items from Ryff's 84 items.…”
Section: Introductionmentioning
confidence: 96%
“…The disproportionate amount of women seeking bariatric surgery lends itself to the strong social stigma assigned to obese women in reflection of pervasive gender-differentiated cultural norms that promote a standard of thinness as the ideal female body shape (Fredrickson andRoberts 1997, Bookwala andBoyar 2008).…”
Section: Treatment Of Obesity and The Impact Of Physical Activitymentioning
confidence: 99%
“…Weight stigmatization reduces psychological well-being, whereby a greater BMI is highly associated with poorer psychological well-being among women, but not men, even when accounting for sociodemographic characteristics (Bookwala and Boyar 2008). Reduced psychological well-being reduces self-efficacy and motivation which in turn may sabotage long-term adoption of health behaviours such as PA .…”
Section: Treatment Of Obesity and The Impact Of Physical Activitymentioning
confidence: 99%
“…Further, examining gender, BMI, and psychological well-being of 3,251 adults ages 25-74, the study found that women with higher BMI scored lower in psychology well-being compared to those with the normal weight. In contrast, men did not show any significant differences between BMI and psychological well-being scores Bookwala and Boyar [30].…”
Section: Introductionmentioning
confidence: 79%